BSCQUAL: A Measuring Instrument of Service Quality for the B-Schools - Nandal , Naveen; Nandal, Nisha (International Journal of Psychosocial Rehabilitation, 2019)
The purpose of this study was to develop and validate BSCQUAL, a new measurement scale of service quality specifically designed for B-School. SERVPREF, SERVQUAL and HEdPERF are the most developed scale in the literature to measure service quality in higher education. A 27 item questionnaire on service quality in B-school was developed and tested for reliability and validity using both exploratory and confirmatory factor analyses. 800 questionnaires were collected out of which only 600 were usable. 300 questionnaires were used for exploratory factor analysis and 300 were used for confirmatory factor analysis SPSS 19 and AMOS 20 were used and exploratory and confirmatory factor analyses were applied. The recommended goodness-of-fit indices of the model were found to be within tolerable ranges, suggesting that the model provides a close fit to the data. The study identified six factors namely Physical evidence, Reliability, Development, Responsiveness, Competence and Delivery as the key dimensions of service quality. Existing literature on services quality has been used in this paper to find the student’s perception and to develops an instrument that provides insights into measuring service quality for BSchool.